2021
DOI: 10.1038/s41598-021-01148-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel findings from family-based exome sequencing for children with biliary atresia

Abstract: Biliary atresia (BA) is a progressive inflammation and fibrosis of the biliary tree characterized by the obstruction of bile flow, which results in liver failure, scarring and cirrhosis. This study aimed to explore the elusive aetiology of BA by conducting whole exome sequencing for 41 children with BA and their parents (35 trios, including 1 family with 2 BA-diagnosed children and 5 child-mother cases). We exclusively identified and validated a total of 28 variants (17 X-linked, 6 de novo and 5 homozygous) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…We examined the frequencies of 60 known BA‐related SNPs in the patient and control groups. These SNPs were selected based on the previous reports 5–28 . We confirmed that the identified SNPs were in Hardy–Weinberg equilibrium.…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…We examined the frequencies of 60 known BA‐related SNPs in the patient and control groups. These SNPs were selected based on the previous reports 5–28 . We confirmed that the identified SNPs were in Hardy–Weinberg equilibrium.…”
Section: Methodsmentioning
confidence: 75%
“…Similarly, the significance of the p.Ala421Thr variant of THOC2 is questionable. Previous WES for 41 Vietnamese BA patients identified this variant in two 9 . However, considering that the allele frequency of this variant in the ToMMo database is as high as 0.013, the p.Ala421Thr variant is unlikely to exert strong deleterious effects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This absence in replication of previously reported de novo variants could be attributed to the genetic ancestry of the study populations or the genetic heterogeneity of BA. For example, two recent family‐based sequencing assessments of BA among Asian children identified variants in novel genes including AMER1 , INVS , OCRL , PCNT , KIF3B , and TTC17 suggesting a genetic heterogeneity of BA (Lam et al, 2021; Tran et al, 2021). The lack of replication and identification of de novo variants across multiple studies highlight the complexity of the etiology of BA and support the hypothesis that isolated BA is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…PKD1L1 encodes Polycystin 1 Like 1 and regulates cilier functions, and both gene defects are associated with visceral heterotaxy. Heterozygous CFC1 and PKD1L1 mutations have been determined in some patients with BASM[ 31 , 32 ]. XPNPEP1 (mediates the metabolism of inflammatory mediators in epithelial cells) and ADD3 (plays a role in the spectrin-actin network in the biliary tract) mutations have been observed in some patients with BA[ 33 ].…”
Section: Biliary Atresiamentioning
confidence: 99%